Perspectives of Islamic and Malay Education on Work Ethics in the Songket Palembang Business Case - Antoni Antoni; Ruskam Sua'idi; Muhammad Amin; Ani Aryati; Eka Yanuarti (STAI Hubbulwathan Duri, 2023)
The purpose of this study was to determine the work ethic of the Palembang songket business case from the perspective of Islamic and Malay education. This study uses a qualitative descriptive analysis method. The data collection used in this study included observation, interviews, documentation and literature studies related to the research objectives regarding the work ethic in the Palembang songket business case. There are two sources of data in this study: first, primary data is original data collected directly from respondents, entrepreneurs, collectors, and Palembang songket workers, as well as observations at the Palembang songket craft business centre. The second type of data used in this research is secondary data, which is collected from other sources such as academic journals, books, and magazines that address issues of conventional work ethics, Islamic texts, and Malay documents. Then analyzed descriptively qualitatively by categorizing, describing, synthesizing, organizing, selecting, and finally drawing conclusions to answer the research problem. Judging from the attitude of persistence, tenacity, discipline, conscientiousness, and patience, this study shows that 1) Perspective of Palembang hardworking songket craftsmen. The work ethic that is built is that work is a calling, actualization, art and worship, which views work as an order from Allah SWT, work seriously and sincerely in order to get good results in accordance with what is done, and a person's work ethic will be judged by Allah, in line with the